2021
DOI: 10.3390/jof7030210
|View full text |Cite
|
Sign up to set email alerts
|

The Abundance and Diversity of Fungi in a Hypersaline Microbial Mat from Guerrero Negro, Baja California, México

Abstract: The abundance and diversity of fungi were evaluated in a hypersaline microbial mat from Guerrero Negro, México, using a combination of quantitative polymerase chain reaction (qPCR) amplification of domain-specific primers, and metagenomic sequencing. Seven different layers were analyzed in the mat (Layers 1–7) at single millimeter resolution (from the surface to 7 mm in depth). The number of copies of the 18S rRNA gene of fungi ranged between 106 and 107 copies per g mat, being two logarithmic units lower than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…This is perhaps not surprising as Layer 1 was characterized microscopically as consisting primarily of diatoms and exopolysaccharides and was the least cohesive and least dense of all layers examined. Moreover, the low numbers of microorganisms detected in Layer 1 is consistent with a recent study based on quantification of eukaryotic microorganisms in the same microbial mat [35]. Microbial mats are well known for their capacity to fix nitrogen and there have been many studies of the distribution of the genes responsible.…”
Section: Discussionsupporting
confidence: 89%
“…This is perhaps not surprising as Layer 1 was characterized microscopically as consisting primarily of diatoms and exopolysaccharides and was the least cohesive and least dense of all layers examined. Moreover, the low numbers of microorganisms detected in Layer 1 is consistent with a recent study based on quantification of eukaryotic microorganisms in the same microbial mat [35]. Microbial mats are well known for their capacity to fix nitrogen and there have been many studies of the distribution of the genes responsible.…”
Section: Discussionsupporting
confidence: 89%
“…As previously described, Kraken2 generated accurate taxonomic identification for bacteria with very fast speed [37,38]. However, only a few studies have used Kraken2 for fungal and viral microbiome studies [39,40]. In this study, we have shown that Kraken2 is a powerful tool for identifying bacteria, fungi, and viruses.…”
Section: Discussionmentioning
confidence: 53%
“…Dothideomycetes constitute almost the entire fungal community in microbial mats from soda lakes and are also found in microbial mats from hypersaline and iron-rich habitats (Gerea et al, 2012;Maza-Márquez et al, 2021;Salano et al, 2017). In microbial mats, fungi play a crucial role in nutrient recycling by decomposing complex carbohydrates into simpler compounds that fuel chemoheterotrophic species (Carreira et al, 2020).…”
Section: Primary Succession Reaches An Equilibrium In Brda Over Few D...mentioning
confidence: 99%